The reproduction of the rhetoric of domestication and violence against women: analysis of content of comments on Facebook - Cabrera, Ximena (2019)
he objective of this article is to analyze the content of the comments issued to El Comercio's digital news item on the Ecuadorian satellite account, which shows that women invest in unpaid care work and domestic activities 1,114 hours per year, while men dedicate 334 annual hours to these activities. This analysis is based on a critical reading from the feminist and gender approach to the comments made by several people regarding the contribution that this unpaid work gives to GDP. Identify the forms of gender discrimination and the reproduction of domestic servitude of women in the opinions made by Facebook to this news.